Study of manufacturing and measurement reproducibility on a laser textured structured surface - MacAulay, Gavin D.; Senin, Nicola; Giusca, Claudiu L.; Leach, Richard K. (Elsevier, 2016)
In recent years there has been increasing interest in the use of structured surfaces to provide specific functional performance. Such surfaces often consist of localised micro-scale surface features with predetermined geometries. The performance of the feature manufacturing process affects the functional performance of the surface, and can be assessed by measurement of the resulting surface features. Measurement of the resulting micromanufactured surface features necessitates use of areal optical surface topography instruments. However, conventional characterisation methods, based on areal surface texture parameters, often prove inadequate, and may fail to capture the relevant geometric properties needed for an effective dimensional verification. This paper investigates an alternative route to verification, based on the determination of geometric attributes of the microfabricated features. This approach allows for direct assessment of manufacturing process performance, by comparison of the geometric attributes with their nominal values. An example application is shown in which a micromachining process (laser texturing) is used to fabricate a periodic pattern of dimples, which provide a low friction bearing surface. In this paper, manufacturing process performance is assessed by characterisation of the diameter and out-of-roundness. Sources of uncertainty associated with these geometric parameters are also considered.